Mollusk communities differ between microenvironments within a shallow lake in the Pampean Region, Argentina - Tietze, Eleonor (2018)
The aim of this study is to compare the faunistic mollusk composition at a local scale, in different sites within a shallow lake, and to evaluate the relation between abundance and richness of mollusks and the environmental variables. The distribution of the mollusks within the water body was patchy but not random. Three of the sites were deeper, mainly dominated by emergent macrophytes and were characterized by the dominance of the gastropods Heleobia parchappii, Physa acuta and Uncancylus concentricus. In contrast, the other two sites were dominated by Biomphalaria peregrina and the bivalve Musculium argentinum, and were characterized by lower depth and pH, and higher vegetation diversity and water temperature. This study evidences the patchiness of freshwater mollusk species in a Pampean shallow lake, where environmental factors partially explain the local distribution within the lake.